Transcranial Alternating Current Stimulation: A Potential Risk for Genetic Generalized Epilepsy Patients (Study Case) - San-Juan, Daniel; Sarmiento, Carlos Ignacio; Hernandez-Ruiz, Axel; Elizondo-Zepeda, Ernesto; Santos-Vázquez, Gabriel; Reyes-Acevedo, Gerardo; Zúñiga-Gazcón, Héctor; Zamora-Jarquín, Carol Marina (Frontiers in Neurology, 2016)
Transcranial alternating current stimulation (tACS) is a re-emergent neuromodulation technique that consists in the external application of oscillating electrical currents that induces changes in cortical excitability. We present the case of a 16-year-old female with pharmaco-resistant juvenile myoclonic epilepsy to three antiepileptic’s drugs characterized by four myoclonic and 20 absence seizures monthly. She received tACS at 1mA@3Hz pulse train during 60 minutes over Fp1-Fp2 (10-20 EEG international system position) during 4 consecutive days using an Endeavor™ IOM Systems device® (Natus Medical Incorporated, Middleton, WI, USA). At the one-month follow-up, she reported a 75% increase in seizures frequency (only myoclonic and tonic-clonic events) and developed a 24h myoclonic status epilepticus that resolved with oral clonazepam and intravenous valproate. At the two-month follow-up, the patient reported a 15-day seizure-free period.